2020
DOI: 10.3892/ijo.2020.5030
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic proteins mediate crosstalk between cancer cells and the tumour microenvironment at primary tumours and metastases (Review)

Abstract: Bone morphogenetic proteins (BMP) are pluripotent molecules, co-ordinating cellular functions from early embryonic and postnatal development to tissue repair, regeneration and homeostasis. They are also involved in tumourigenesis, disease progression and the metastasis of various solid tumours. Emerging evidence has indicated that BMPs are able to promote disease progression and metastasis by orchestrating communication between cancer cells and the surrounding microenvironment. The interactions occur between B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 220 publications
(306 reference statements)
0
7
0
Order By: Relevance
“…MMPs (matrix metalloproteinases) influence tumour invasion and cancer cell migration which can be regulated by BMPs (4,18). ACVRL1, GDF6, BMP8A, ACVR1 and GREM1 were seen as the top five genes which were positively correlated with the MMPs while ACVR1B, ACVR2B, GDF9, DAND5, BMPR1B were ranked as the top five being negatively correlated.…”
Section: Correlation Between Bmps and Epithelial Mesenchymal Transiti...mentioning
confidence: 99%
See 1 more Smart Citation
“…MMPs (matrix metalloproteinases) influence tumour invasion and cancer cell migration which can be regulated by BMPs (4,18). ACVRL1, GDF6, BMP8A, ACVR1 and GREM1 were seen as the top five genes which were positively correlated with the MMPs while ACVR1B, ACVR2B, GDF9, DAND5, BMPR1B were ranked as the top five being negatively correlated.…”
Section: Correlation Between Bmps and Epithelial Mesenchymal Transiti...mentioning
confidence: 99%
“…Previous studies have reported that there are over 20 BMP ligands, which are transduced by seven type I and five type II transmembrane serine/threonine kinase receptors (3). They were originally found in bones, playing a critical role in endochondral bone growth, embryonic development, tissue repair and homeostasis and stemness (4). Upon interaction with the BMP ligands, the Type-II receptors phosphorylate the Type-I receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of BMP4 in proper PS and mesoderm development has been well documented [20,37], and it is known to be secreted from the amnion during mesoderm induction [50]. However, BMP4 and EGF could be redundant during ExM formation, possibly via the common PI3K/AKT and/or MAPK pathway [97]. Additionally, the two protocols also contain other components with opposing effects.…”
Section: Discussionmentioning
confidence: 99%
“…These interactions direct the functions of tumor and stromal cells in the niche to promote the initiation of tumor growth, angiogenesis, local invasion, and metastasis. This leads to the establishment of cancer cells in the tumor niche (Sun et al, 2020). Extracellular antagonists such as chordin, noggin, follistatin, cerberus,g-1, and tolloid, can bind to BMPs and inhibit their interaction with corresponding receptors (Zylbersztejn et al, 2018).…”
Section: Aging and Cancermentioning
confidence: 99%